Study on the effect of 3,5,6,7,8,3′,4′-heptamethoxyflavone in Fructus Aurantii by regulating intestinal aquaporin in body fluids - Ting-Ting Bai; Ting-Ting Bai; Ya-Ting Xie; Quan Wan; Jin-Lian Zhang (Frontiers in Pharmacology)
BackgroundFructus aurantii (FA) can cause the drying of body fluids, although the specific mechanism of this process remains unclear. FA is used to promote stagnation and eliminate flatulence in traditional Chinese medicine. 3,5,6,7,8,3′,4′-heptamethoxyflavone is the active metabolite in FA, and it contributes to the drying process. This paper presents an investigation into the underlying mechanisms of the effect of 3,5,6,7,8,3′,4′-heptamethoxyflavone on body fluids through regulating the Aquaporin pathway.MethodsHuman small intestinal epithelial cells (FHs74lnt), human colon histiocytes (CCD018Co), a normal mouse, and an AQP3 knockout mouse, were used in the study. Indicators included the water consumption, diet, and fecal water content of the mice, as well as pathological changes in the small intestinal and colon tissues and the relative expression of AQP3, AQP5, AQP7, and AQP11 mRNA in those tissues, and protein expression. ALD and ADH hormone levels, and the AQP3 upstream receptor genes AVPR1 and AVPR2 were also used as indicators for examination.Results3,5,6,7,8,3′,4′-heptamethoxyflavone has a strong desiccating impact on body fluids, causing an increase in water intake and a rise in the water content of feces. Additionally, animal experiments have suggested a connection to histological damage in the colon and small intestine, including lymphocyte infiltration, mucosal laminae breakage, and local ulceration. Additionally, the expression of the proteins Aquaporin 3, 5, 7, and 11 in the intestinal tissues may be regulated by 3,5,6,7,8,3′,4′-heptamethoxyflavone. This metabolite also increases the expression of upstream receptor genes, allowing them to bind more easily to antidiuretic hormone and aldosterone, such as arginine vasopressin receptors 1 and 2. A number of changes in water intake and fecal water content were observed in response to 3,5,6,7,8,3′,4′-heptamethoxyflavone in experiments conducted on Aquaporin3−/− mice. The control of water secretion and absorption in the body is thus impacted by alternating the Aquaporin 3 water channels.Conclusion3,5,6,7,8,3′,4′-heptamethoxyflavone may affect upstream receptor genes, including AVPR1 and AVPR2, and promote their binding to ALD and ADH, which in turn affects the opening and closing of the AQP3 water channel to regulate water secretion and absorption in the body.